Performa Ayam Kampung Unggul Balitnak (KUB) dengan penambahan dedak fermentasi dalam ransum - Emy Saelan; Sulasmi; Sri Utami; Muhammad Ade Salim (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
Kampung Unggul Balitnak (KUB) is a native chicken crossed for six generations. Rice bran is an energy source of feed, but rice bran has high crude fiber. The research was conducted in the poultry production cage of Sasa Village, South Ternate City. This study aimed to determine the percentage of fermented rice bran of performance of KUB Village chicken for meat production. The study used a Completely Randomized Design (CRD) consisting of five treatments and four replications. Data obtained were analyzed with Analysis of Variance (ANOVA) one way and further tests with Duncan Multiple Range Test (DMRT). The results showed that the ration consumption for all treatments (R0, R1, R2, R3, and R4) was not significantly different (p>0.05). The body weight gain, feed conversion, and carcass weight were not significantly different (p>0,05) between R0, R1, R2, and R3 treatments. However, the R4 treatment showed significant differences (p<0.05) from the other treatments. In conclusion, presenting a ration containing up to 30% fermented rice bran provides optimal results for the growth of KUB chicken to produce meat.